Efficacy and safety of adjunctive lacosamide in the treatment of primary generalised tonic-clonic seizures: a double-blind, randomised, placebo-controlled trial. Issue 10 (18th August 2020) - Vossler, David G; Knake, Susanne; O'Brien, Terence J; Watanabe, Masako; Brock, Melissa; Steiniger-Brach, Björn; Williams, Paulette; Roebling, Robert
Abstract : Objective: To evaluate efficacy and safety of lacosamide (up to 12 mg/kg/day or 400 mg/day) as adjunctive treatment for uncontrolled primary generalised tonic-clonic seizures (PGTCS) in patients (≥4 years) with idiopathic generalised epilepsy (IGE). Methods: Phase 3, double-blind, randomised, placebo-controlled trial (SP0982; NCT02408523 ) in patients with IGE and PGTCS taking 1–3 concomitant antiepileptic drugs. Primary outcome was time to second PGTCS during 24-week treatment. Results: 242 patients were randomised and received ≥1 dose of trial medication (lacosamide/placebo: n=121/n=121). Patients (mean age: 27.7 years; 58.7% female) had a history of generalised-onset seizures (tonic-clonic 99.6%; myoclonic 38.8%; absence 37.2%). Median treatment duration with lacosamide/placebo was 143/65 days. Risk of developing a second PGTCS during 24-week treatment was significantly lower with lacosamide than placebo (Kaplan-Meier survival estimates 55.27%/33.37%; HR 0.540, 95% CI 0.377 to 0.774; p<0.001; n=118/n=121). Median time to second PGTCS could not be estimated for lacosamide (>50% of patients did not experience a second PGTCS) and was 77.0 days for placebo. Kaplan-Meier estimated freedom from PGTCS at end of the 24-week treatment period (day 166) for lacosamide/placebo was 31.3%/17.2% (difference 14.1%; p=0.011). More patients on lacosamide than placebo had ≥50% (68.1%/46.3%) or ≥75% (57.1%/36.4%) reduction from baseline in PGTCS frequency/28 days, or observed freedom from PGTCS during treatment (27.5%/13.2%) (n=119/n=121). 96/121 (79.3%) patients on lacosamide had treatment-emergent adverse events (placebo 79/121 (65.3%)), most commonly dizziness (23.1%), somnolence (16.5%), headache (14.0%). No patients died during the trial. Conclusions: Lacosamide was efficacious and generally safe as adjunctive treatment for uncontrolled PGTCS in patients with IGE.